Rehabilitation interventions - Turk, Margaret A.; Mudrick, Nancy R. (Thousand Oaks, Calif. : SAGE Publications, Inc., 2013)
Explores issues involving rehabilitation interventions and therapies and examines topics central to the lives of individuals with disabilities and their families.
Ch 1. Introduction, background, and history -- ch 2. Current issues, controversies, and solutions -- ch 3. Chronology of critical events -- ch 4. Biographies of key contributors in the field -- ch 5. Annotated data, statistics, tables, and graphs -- ch 6. Annotated list of organizations and associations -- ch 7. Selected print and electronic resources.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: People with disabilities -- Rehabilitation; Medical rehabilitation; People with disabilities -- Medical care; Healing; People with disabilities -- Services for; People with disabilities -- Functional assessment; Rehabilitation; Rehabilitation; Persons with Disabilities -- rehabilitation; Recovery of Function; Personnes handicapées -- Intégration.; Personnes handicapées -- Services; Personnes handicapées -- Évaluation fonctionnelle; Réadaptation.; Personnes handicapées -- Services de santé.; Guérison.; pardons; MEDICAL -- Physical Medicine & Rehabilitation; Rehabilitation; People with disabilities -- Services for; People with disabilities -- Functional assessment; Healing; Medical rehabilitation; People with disabilities -- Medical care; People with disabilities -- Rehabilitation